Refinements of Bounds for Neuman Means - Yu-Ming Chu; Wei-Mao Qian (Abstract and Applied Analysis)
We present the sharp bounds for the Neuman means SHA, SAH, SCA and SAC in terms of the arithmetic, harmonic, and contraharmonic means. Our results are the refinements or improvements of the results given by Neuman.